The impact of the cost by processes and the productive chain of asparagus in agro-exports - Risco-Mc Gregor, Nelly Adriana (2022)
Objective: To demonstrate the positive impact of the cost system for processes in the productive chain of asparagus in agro-export companies, this given the need to know, in a reliable way, their costs and that this, in turn, allows them to improve the taking of decisions. Method: The research was descriptive and the research design was nonexperimental. For our analysis, the case study was applied to the company Vivadis Perú S.A.C., a company dedicated to the agro-export of asparagus. Results: The process costs system, applied to the asparagus production chain, allowed to determine more precisely the costs that are managed by materials and labor in each of the stages of the asparagus production process compared to a system of costing managed in an empirical way whose data are very general. This accounting activity will make it possible to project investment in agro-exports. Conclusion: The process cost system has a favorable impact on the asparagus production chain, both in the application of raw material and in the labor used in each process of the production chain.